Clonal Dissemination of Clinical Carbapenem-Resistant Klebsiella pneumoniae Isolates Carrying fosA3 and blaKPC–2 Coharboring Plasmids in Shandong, China - Hao, Yingying; Zhao, Xuguang; Zhang, Cui; Bai, Yuanyuan; Song, Zhen; Lu, Xinglun; Chen, Ran; Zhu, Yaoyao; Wang, Yueling (Frontiers in Microbiology, 2021)
Treatment strategies of infection by carbapenem-resistant Klebsiella pneumoniae (CRKP) are limited. Fosfomycin, a broad-spectrum antibiotic, has attracted renewed interest in combination therapy to fight K. pneumoniae infections. However, reports on fosfomycin-resistant K. pneumoniae are increasing. Among the 57 CRKP strains, 40 (70.2%) were resistant to fosfomycin. Thus, whole-genome sequencing and bioinformatics analysis were conducted to reveal molecular characteristics of fosfomycin-resistant K. pneumoniae. Twenty-three isolates coharbored fosAkp and fosA3, with K. pneumoniae carbapenemase (KPC)-producing ST11-KL64-wzi64-O2 (n = 13) and ST11-KL47-wzi209-OL101 (n = 8), the predominating clonal groups, while fosA3 was not detected in isolates carrying class B carbapenemase genes. Twenty-two (out of 26) ST11-KL64 strains were positive for rmpA2, of which 12 carried fosA3. Four of the 23 fosA3-positive isolates could successfully transfer their fosfomycin-resistant determinants to Escherichia coli J53AziR. All four strains belonged to ST11-KL47 with the same pulsed-field gel electrophoresis profile, and their transconjugants acquired fosfomycin, carbapenem, and aminoglycoside resistance. A 127-kb conjugative pCT-KPC-like hybrid plasmid (pJNKPN52_KPC_fosA) coharboring fosA3, blaKPC–2, blaCTX–M–65, blaSHV–12, rmtB, and blaTEM–1 was identified. ST11-KL64 and ST11-KL47 K. pneumoniae, with higher resistance and virulence, should be critically monitored to prevent the future dissemination of resistance.